Competition leverage: how the demand side affects optimal risk adjustment. (December 2014) - Bijlsma, Michiel; Boone, Jan; Zwart, Gijsbert
<x xml:space="preserve">Abstract</x> We study optimal risk adjustment in imperfectly competitive health insurance markets when high‐risk consumers are less likely to switch insurer than low‐risk consumers. Insurers then have an incentive to select even if risk adjustment perfectly corrects for cost differences. To achieve first best, risk adjustment should overcompensate insurers for serving high‐risk agents. Second, we identify a trade‐off between efficiency and consumer welfare. Reducing the difference in risk adjustment subsidies increases consumer welfare by leveraging competition from the elastic low‐risk market to the less elastic high‐risk market. Third, mandatory pooling can increase consumer surplus further, at the cost of efficiency.